1985
DOI: 10.1002/ajh.2830200408
|View full text |Cite
|
Sign up to set email alerts
|

The incidence of thrombotic and hemorrhagic disorders in association with extreme thrombocytosis: An analysis of 129 cases

Abstract: We have presented a retrospective study of 129 patients with platelet counts of 1,OOO X 109/L or more-72 with myeloproliferative disorders (MPD), and 57 with reactive thrombocytosis (RT)-in an effort to determine the incidence of thrombohemorrhagic complications. Thrombotic disorders occurred with approximately equal frequency in the two groups, being found in three patients (4%) with MPD and three (5%) with RT when the platelet count was over 1,OOO X 109/L and in 11% of the patients in each group when the pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
68
0
3

Year Published

1988
1988
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(73 citation statements)
references
References 10 publications
2
68
0
3
Order By: Relevance
“…In a study of 129 patients with extreme thrombocytosis (>1,000 G/l), 72 in MPD and 57 with reactive thrombocytosis, thrombosis was found in 3-4% [18], but a prospective observational study of patients with essential thrombocythemia (ET) and a platelet count <1,500 G/l as compared to an age-and sex-matched control group failed to show an increased risk for thrombosis in ET patients [19]. A recent study investigating etiology and clinical significance of thrombocytosis found a higher incidence of venous and arterial thrombosis in patients with primary thrombocytosis as compared to patients with secondary thrombocytosis (12.4% vs. 1.6%).…”
Section: Discussionmentioning
confidence: 99%
“…In a study of 129 patients with extreme thrombocytosis (>1,000 G/l), 72 in MPD and 57 with reactive thrombocytosis, thrombosis was found in 3-4% [18], but a prospective observational study of patients with essential thrombocythemia (ET) and a platelet count <1,500 G/l as compared to an age-and sex-matched control group failed to show an increased risk for thrombosis in ET patients [19]. A recent study investigating etiology and clinical significance of thrombocytosis found a higher incidence of venous and arterial thrombosis in patients with primary thrombocytosis as compared to patients with secondary thrombocytosis (12.4% vs. 1.6%).…”
Section: Discussionmentioning
confidence: 99%
“…41,50 The thrombotic risk seen with elevated white blood cells may be related to JAK2V617F allele burden, 54 and should be evaluated and carefully incorporated in the risk stratification for deciding whether a patient should be started on cytoreductive treatment. Extreme thrombocytosis is associated with increased hemorrhagic risk, 55 but does not seem to be a risk factor for thrombotic events. Moreover, recent evidence suggests that outside of age and prior thrombotic events, even at extreme levels high platelet counts may not be all predictive for thrombotic events.…”
Section: Venous Thromboembolism In Et and Pv H Reikvam And Rv Tiumentioning
confidence: 96%
“…It has been suggested that thrombocytosis can contribute to the vascular events of essential thrombocytosis or polycythaemia vera, since platelet count reduction was reported to lower the risk of microcirculatory disturbances and the antithrombotic efficacy of chemotherapy in high-risk essential thrombocytosis subjects has been clearly demonstrated [25,32,41,42]. Essential thrombocytosis patients with microvascular disturbances have decreased platelet survival and evidence for platelet-mediated thrombotic processes, such as increased urinary thromboxane B2 [21].…”
Section: Aetiologymentioning
confidence: 99%